PEMANFAATAN EKSTRAK JINTAN HITAM UNTUK MENURUNKAN KADAR ENZIM LP-PLA2 SEBAGAI KANDIDAT PENGOBATAN ATEROSKLEROSIS - Retno Susilowati; Evika Sandi Savitri; Kholifah Holil (The East Java Biological Society, 2012)
Ox-LDL deposits in the sub-endothelial easily occur in individuals who have hyperlipidemia accompanied with oxidative stress. The enzyme Lp-PLA2 is an enzyme marker of three proaterogenik conditions, those are hyperlipidemia, oxidative stress and inflammation. Black cumin seeds (Nigella sativa L.) have antioxidants ingredient that can inhibit lipid peroxidation, and expected to inhibit atherosclerosis through decreased levels of the enzyme Lp-PLA2 and F2-Isp. This study used posttest only control group design using experimental animals Rattus norvegicus Wistar males. The study analysied the number of foam cells, lipid profi le, Lp-PLA2 andF2-Isp plasma levels in hyperlipidemia rats were given extracts of black cumin seeds with 3 different doses (0; 3.6 and 7.2 mg / kg). The results showed that the extract of black cumin seeds can decrease serum levels of Lp-PLA2, tend to reduce the formation of foam cells,but not signifi cant to decreasing levels of F2-Isp. Black cumin seeds extract can decrease cholesterol, TG, LDL and increase HDL in the blood serum. The extract of black cumin seeds is anti atherogenic by reducing the enzyme Lp-PLA2 and improve lipid profi les.